PWE-428 Oesophageal ph/manometry – the trainees' perspective. (22nd June 2015) - Stasinos, I; Birdi, S; Jayakumar, S; Jayasundera, J; Sattianayagam, P
Abstract : Introduction: Oesophageal disorders are among the commonest medical conditions.¹ Management of these conditions is a core competence in the curriculum of gastroenterology trainees. 2 British Society of Gastroenterology (BSG) guidelines outline the uses of oesophageal pH/manometry assessment in establishing oesophageal diagnoses and targeting relevant treatments.¹ Method: We aimed to assess the trainees' knowledge and experience of oesophageal pH/manometry as per JRCPTB guidelines.² An anonymous survey of gastroenterology trainees in Kent Surrey and Sussex and North East London deaneries was carried out. A questionnaire was sent out twice over a one month period (November 2014) and responses were assessed. Results: 23/70 (33%) completed the survey. 5/23 were in their 1 st year of training, 4/23 in their 2 nd, 6/23 in their 3 rd, 6/23 in their 4 th and 2/23 in their 5 th . Training: 22 of trainees replied. No trainee had done research in the field. 13/22 (59%) trainees had teaching on oesophageal physiology at a regional training day at some point during their training and four of these had also attended lectures on this field at a national/international meeting. 1/22 (4.5%) had only attended lectures at a national/international meeting and 8/22 (36%) trainees had no training or education at all. 16/23 (70%) had read all or part of any BSG guidelines and 8/23 (35%) had read the BSG guidelines on oesophageal/pH manometry. Only 4/23 (17%) felt that their training in this area was satisfactory. Understanding: 16/23 (70%) trainees listed at least one indication for oesophageal pH assessment. Only 3/23 (13%) were able to list more than two indications. 15/23 (65%) would request manometry studies for suspected oesophageal motility disorders. 7/23 (30%) knew of its use as a pre-assessment prior to fundoplication. 15/23 (65%) knew that an oesophageal pH below 4 is indicative of significant gastro-oesophageal reflux disease and 5/23 (22%) were familiar with the DeMeester score. Technical ability: 17/23 (74%) had worked in hospitals with oesophageal pH/manometry facilities. No trainee had "hands-on" experience and only 4/23 (17%) had seen it performed at all. 21/23 (91%) said that they would like to further their knowledge and expertise in the area. 18/23 (78%) felt that it might improve job prospects. Conclusion: Education and training in oesophageal pH/manometry is deficient despite this area being recognised in the gastroenterology curriculum and available in hospitals in the South-East. There is scope for improvements in both areas. Disclosure of interest: None Declared. References: British Society of Gastroenterology: Guidelines for oesophageal manometry and pH monitoring (Nov 2006)-K. Bodger and N. Trudgill Joint Royal College of Physicians Training Board (2010) – Higher Medical Training Curriculum for Gastroenterology